A Proposed Framework for Facilitating Social and Environmental Responsibility in Life Orientation through Environmental Education in the South African Context. Issue 4 (4th July 2019) - Swarts, Pieter; Rens, Julialet A.; de Sousa, Luiza O.
Abstract: Life Orientation (LO) is judged by the Department of Basic Education to be critical for the development of social and environmental responsible behaviour among South African schoolchildren. Despite this crucial role, the research revealed that the participants in the study reported on do not succeed as expected with the fostering of competencies regarding social and environmental responsible knowledge, values and skills, as required by the South African Curriculum and Policy Assessment Statement. The research findings as obtained through structured classroom observations and semi-structured interviews and reported here, inspired the researchers to develop a generic and holistic framework which can assist LO teachers with the facilitation of social and environmental responsible knowledge, values and skills in a more positive and learner-centred way through environmental education.